Komunikasi Berdasarkan Tradisi (Retorika, Semiotik, Fenomologi, Psikologi Sosial, Sibernetik, Sosio Kultural, Kritis) - Winda Kustiawan; Masnawari Harahap; Intan Tursina; Ummil Khoiriyah; M. Fathih Ichtisam; Barkah Anshori; Thahirah Azzahra (Maktabatun: Jurnal Perpustakaan dan Informasi, 2021)
Communication is "the process by which one or more individuals, groups, organizations, and communities create and use information about their environment and about other individuals." Communication is verbal and non-verbal. (Dr. Samshia:2017) It has seven communication traditions, including rhetoric, semiotics, phenomenology, cybernetics, social psychology, sociocultural traditions, and critical or artistic communication, either directly or indirectly with society and the environment. I'm talking about interaction. The conclusion of the study is that human beings have complex personalities that manifest in various situations and interactions. In the process of surface (imaging), the outer layer is adapted to the appearance